2019
DOI: 10.3390/v11090848
|View full text |Cite
|
Sign up to set email alerts
|

A 19 Year Analysis of Small Mammals Associated with Human Hantavirus Cases in Chile

Abstract: Small mammals present in areas where hantavirus cardiopulmonary syndrome (HCPS) cases had occurred in central and southern Chile were captured and analyzed to evaluate the abundance of rodents and seroprevalence rates of antibodies to Andes orthohantavirus (ANDV). Sampling areas ranged from the Coquimbo to Aysén regions (30–45° S approx.) regions. Ninety-two sites in peridomestic and countryside areas were evaluated in 19 years of sampling. An antibody against ANDV was detected by strip immunoassay in 58 of 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…A study conducted in Chile [ 46 ], during 19 years of sampling eleven rodent species, evaluated how ecology and geography influence host and viral dynamics in areas associated with HI cases in that country, finding that the main ANDV reservoir is O. longicaudatus with an intraspecific seroprevalence of 6.5%. They also point out the need for research on rodents’ social and behavioral interactions, highlighting the integration of ecological understanding of the host and pathogens, spatial and temporal surveillance, epidemiology, and public health agencies, as fundamental to understanding the transmission of the virus to humans.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Chile [ 46 ], during 19 years of sampling eleven rodent species, evaluated how ecology and geography influence host and viral dynamics in areas associated with HI cases in that country, finding that the main ANDV reservoir is O. longicaudatus with an intraspecific seroprevalence of 6.5%. They also point out the need for research on rodents’ social and behavioral interactions, highlighting the integration of ecological understanding of the host and pathogens, spatial and temporal surveillance, epidemiology, and public health agencies, as fundamental to understanding the transmission of the virus to humans.…”
Section: Discussionmentioning
confidence: 99%
“…These include but are not limited to Andes virus ( Orthohantavirus andesense , ANDV) from Oligoryzomys longicaudatus ; Black Creek Canal virus ( Orthohantavirus nigrorivense , BCCV) from Sigmodon hispidus ; New York virus (NYV) from Peromyscus leucopus ; Choclo virus ( Orthohantavirus chocloense , CHOV) and Maporal Virus ( Orthohantavirus maporalense , MAPV) from Oligoryzomys fulvescens ; Rio Mamore virus (RIOMV) from Oligoryzomys microtis ; Bayou virus (BAYV) from Oryzomys palustris ; Laguna Negra virus ( Orthohantavirus negraense , LANV) from Calomys laucha ; and Juquitiba virus (JUQV) from Oligoryzomys nigripes [ 5 , 11 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. In South America, clinical cases of HCPS have been reported in Argentina [ 24 ], Uruguay [ 25 ], Brazil [ 26 ], Chile [ 27 , 28 ], Bolivia [ 29 ], Peru [ 30 , 31 ], and Paraguay [ 32 ]. In Brazil, JUQV and Araraquara virus (ARAV, reservoir: Necromys lasiurus) are the two strains that have been discovered in patients [ 33 ], and about 85% of HCPS cases reported in Brazil have occurred in a region where O. nigripes , the reservoir of JUQV, is endemic [ 26 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The collaboration [ 80 ] resulted in >11,000 archived specimens over 2 decades, which now serve as a foundation for continued monitoring of and research into hantaviruses and their hosts, in addition to other symbionts and pathogens. Similar responses to HPS emergence in Chile and Argentina spawned parallel specimen-based research efforts that identified new hantavirus strains in a number of rodent species [ 81 83 ], underscoring the power of public health–biorepository collaborations to build comprehensive biological archives useful for EID research and response. Fundação Oswaldo Cruz (Fiocruz, Brazil) provides another precedent of successful biorepository and public health integration to maximize EID research and response.…”
Section: Introductionmentioning
confidence: 99%